DINAMIKA POLITIK; SOLUSI AKHIR EKSISTENSI KONFLIK DAN PENGARUHNYA TERHADAP MASYARAKAT PASCA PERDAMAIAN DI ACEH BESAR - Usman Usman; Cut Megawati (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2017)
This study was aimed to investigate whether there is still an effort to maintain the final solution of conflict existence in the politic and its impact to the society after the peace agreement has been signed. This study used the descriptive qualitative approach by using interview and observation as data collection. The research findings revealed several indicators of conflict existence; they were unfairness, dishonesty, structured, massive and sistematic fraud that is still occured in politic democratic such as black campaign and money politics. As the impact, these indicators remain as a trigger of conflict that cause violence acts in the society in almost every part of Aceh which also occured in Aceh Besar. The most likely impact in the society was a demonstration which often happen in a campaign that often followed by violence acts, terror, and also intimidation